Surfactant-Assisted Synthesis of Zn(suc)(ina)2 Metal-Organic Framework and Detection of Nitroaromatic Explosives - Wang, Wei; Chi, Bo-Wei; Shao, Guo-Quan; Si, Jing-Yu; Wu, Yun; Tian, Chang-An (Asian Journal of Chemistry, 2013)
Some traditional techniques, such as hydrothermal synthesis, microemulsion techniques and solvothermal synthesis, are applied to prepare metal-organic frameworks and non-metal-organic frameworks. In this article, we present a morphology-controlled synthesis of non-metal-organic frameworks by using a surfactant-assisted method for potential fluorescent sensing of nitroaromatic explosives. Nanocrystals of three-dimensional (3-D) metal-organic frameworks, Zn(suc)(ina)2. The structures was confirmed by transmission electron microscopy. TEM images of Zn(suc)(ina)2 reveal that size and shape of nanocrystals can be tuned by varying the reaction time. Fluoresent sensing of nitrobenzene to nanocrystal has been studied. The results indicate that nanocrystals of metal-organic frameworks Zn(suc)(ina)2 is highly sensitive to nitroaromatic compounds. The results may be helpful for designing novel fluorescence sensor for the sensing of explosives.